Meningkatkan Potensi dan Kreativitas Siswa di MAN 1 Sarolangun melalui Kegiatan Terstruktur - Dismawati; Putri, Riska Meisyi; Mardalena (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Creativity is one of the essential competencies for students in facing the challenges of the 21st century, because this ability enables individuals to think critically, innovatively, and produce new solutions that are relevant and useful. At MAN 1 Sarolangun, students' creative potential has not been fully explored due to the dominance of conventional learning methods that are more theoretical, so that students' creative ideas are not optimally channeled. Structured socialization activities are believed to be an effective strategy to foster understanding, motivate, and develop students' creativity systematically. This study aims to design and implement creative socialization activities through a series of structured activities that include creativity workshops, group discussions, creative mini projects, idea competitions, and reflection and evaluation of activity results. The method used is community service with instruments in the form of creativity observations before and after the activity, documentation, and participatory evaluation. The activity was carried out on Wednesday, December 10, 2025, involving students of grades X–XII of MAN 1 Sarolangun. The results of the implementation of the activity were an increase in student creativity scores, the emergence of innovative ideas that can be applied in school assignments and activities, and the formation of a participatory and innovative culture. These findings are expected to be the basis for developing creative learning strategies at MAN 1 Sarolangun, as well as being a model that can be adapted by other schools to foster student creativity in a sustainable manner.